Acyrlamide degrader and method of utilizing the same - Abd. Shukor, Mohd. Yunus; Syed, Mohd Arif; Abdul Rahim, Mohd Badrin Hanizam (2011)
The present invention relates to a newly isolated biogically pure culture of Rhodotorula sp. Strain MBH23 with accession number KCTC 11960BP. The biogically pure culture is capable of degrading acrylamide compound up to 1500 mg/L. Furthermore, the present invention provides a method of treating acrylamide pollution by utilizing the biogically pure culture. The biogically pure culture is contacted with the acrylamide compound resulting in the conversion of toxic acrylamide to non-toxic product.